Judaísmo e direitos humanos: um estudo das contribuições judaicas na tessitura dos direitos humanos - Dellova, José Pietro Buono Nardelli (2021)
Work that was developed and based on the principled idea of love, as well as the Jewish experience as an emancipatory movement and respective elective affinities with Human Rights. It is shown here that Judaism is not a revealed religion, but built on multicultural bases and, for that very reason, it has a universal character, as well as Human Rights. The concepts of elective affinities and tessitura (a term borrowed from the musical area) are fundamental to the understanding of Judaism and respective relationship with Human Rights. This work presents Human Rights as a continuous movement as well as the characteristic human Judaism, under which Jewish men and Jewish women remain throughout history